Country study Albania - Tarelli I.; Dano S. (Study of the organic and safety agriculture in the Adriatic cross-border region and of training needs, 2007)
The objective of this study is to provide a description of the agro-food scenario of the country, the main production sectors, the actual substantial character of organic farming and its development potentialities. The training needs of the institutional subjects mainly involved in the management of the organic agriculture system have been particularly evaluated. The difficulties for the development of analyses are the limited availability of the information sources.